Die Schreibungen des Wortes etinnu “Baumeister” im Neuassyrischen - Deller, Karlheinz
meist LÚTIN geschrieben; ABL 102; ABL 253 (K. 1175 + K. 1179 + K. 1207); ABL 389; ABL 955; K. 1902 + K. 13158 + K. 13161; ABL 1178; ABL 476.